2021
DOI: 10.1111/cdev.13636
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ Preference for Social Interactions Increases from 7 to 13 Months of Age

Abstract: This study examined 7-to-13.5-month-old middle-class Western infants' visual orienting to third-party interactions in parallel with their social attention behavior during own social interactions (Leipzig, Germany). In Experiment 1, 9.5-to-11-month-olds (n = 20) looked longer than 7-to-8.5-month-olds (n = 20) at videos showing two adults interacting with one another when simultaneously presented with a scene showing two adults acting individually. Moreover, older infants showed higher social engagement (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…Ethical approval for the design and procedure of the study “Observing others’ joint attention increases 9-month-old infants’ object encoding” was provided by the Child Subjects Committee of the Max Planck Institute for Evolutionary Anthropology (no protocol number). We preregistered the hypotheses, methods, procedures, and the data analysis plan for this experiment on the Open Science Framework (OSF; https://osf.io/yfegm/ [Thiele et al, 2020a]). Video examples, eye tracking raw data, and R scripts for preprocessing and analyzing the data are available at the same link on the OSF.…”
Section: Methodsmentioning
confidence: 99%
“…Ethical approval for the design and procedure of the study “Observing others’ joint attention increases 9-month-old infants’ object encoding” was provided by the Child Subjects Committee of the Max Planck Institute for Evolutionary Anthropology (no protocol number). We preregistered the hypotheses, methods, procedures, and the data analysis plan for this experiment on the Open Science Framework (OSF; https://osf.io/yfegm/ [Thiele et al, 2020a]). Video examples, eye tracking raw data, and R scripts for preprocessing and analyzing the data are available at the same link on the OSF.…”
Section: Methodsmentioning
confidence: 99%
“…Jones and Klin (34) observed that 2-to 6-month-old male infant siblings who went on to receive the diagnosis of ASD did not display evidence of less looking to faces and eyes at the end of the neonatal period of development (see Figure 3). One of the issues that may have impacted the observations of Jones and Klin (34) is the bias for attention to faces may be weak or highly variable in the first months of life in typical development, but become more evident or consistent among 6-to 12-month-olds (86)(87)(88). Hence, the typical pattern of social attention development in neonates may not be sufficiently robust or reliable to readily detect contrasting atypical patterns of development.…”
Section: The Timing Of the Development Of Social Orienting And Joint Attention Symptomsmentioning
confidence: 99%
“…Computational models of gaze following development have successfully simulated the social reinforcement learning processes, suggesting the existence of a social motivation factor (Carlson & Triesch, 2004;Ishikawa et al, 2020). Similarly, a recent study in human infants reported that infants show increasing attentiveness to others' social interactions from 7-to 14-month of age, which develop in parallel to improvements in their joint attention during parent-infant free-play interactions (Thiele et al, 2021). Likewise, our eye tracking measures of social orienting and social reward processing appear to be indicators of a latent social motivation factor that predicts the development of gaze following.…”
Section: Early Infant Social Motivation Predicts Later Gaze Followingmentioning
confidence: 88%